2016
DOI: 10.1007/s40890-016-0011-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Roadside Friction on Travel Speed and LOS of Rural Highways in India

Abstract: Substantial amount of money has been invested by Government of India and several State Governments to improve the level of service of various categories of roads in India. Roads have been widened and strengthened, surface condition has been improved but Level of Service has not been improved as expected because of various socioeconomic factors. One of the important factors has been the presence of side friction along Indian rural highways. Existence of road-side markets at regular interval along rural highways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…For example, road segments with schools and wet markets tend to have a higher roadside friction. The speed-flow curve illustrated in Figure 4 was adopted for this case study, with reference to the paper of Pal and Roy [49]. A regression equation was fitted to the speed-flow curve shown on Figure 4.…”
Section: Data Collection For the Illustrative Case Studymentioning
confidence: 99%
“…For example, road segments with schools and wet markets tend to have a higher roadside friction. The speed-flow curve illustrated in Figure 4 was adopted for this case study, with reference to the paper of Pal and Roy [49]. A regression equation was fitted to the speed-flow curve shown on Figure 4.…”
Section: Data Collection For the Illustrative Case Studymentioning
confidence: 99%
“…The second group falls in development of speed-density and speed-flow curves for with and without side friction cases. Traffic flow models like Greenshields, Greenberg, etc., were fitted, using which capacity and LOS reduction due to side friction were calculated [10][11][12][13][14]. Since the focus of the present study is on relating friction parameters with the speed through regression analysis, the studies on the same were reviewed below.…”
Section: Introductionmentioning
confidence: 99%
“…Roadside friction (RSF) elements have become a serious factor causing congestion and poor traffic operation in urban and rural road networks in developing countries (Salini et al, 2014;Harison et al, 2016;Pal and Roy, 2016). Many urban roads in developing countries cities have a low level of service (LOS) and hence poor performance due to some activities that take place on and alongside roads (Rao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Harison et al (2016) observed that one of the factors affecting traffic mobility is roadside friction (RSF). (Pal and Roy, 2016) found that pedestrians moving randomly across the carriageway affect traffic operation even if traffic volume is low. Road designers often assume that pedestrians cross roadways at designated pedestrian crossings, which include intersection crosswalks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation